A PILOT STUDY ON THE EFFECT OF CATHA EDULIS FROSK., (CELASTRACEAE) ON METABOLIC SYNDROME IN WOKW RATS - Mahmood, Samira Abdulla; Lindequist, U. (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
This study investigated the effect of Catha edulis (khat) on some important parameters of the metabolic syndrome in Wistar Ottawa Karlsburg W (WOKW ) rat. The animals were fed with the standard chow containing 5% air dried pulverized khat leaves for 14 days; followed by the standard chow for16 days. The khat leaves were sorted into green (khat light; KL) and crimson (khat dark; KD) leaves. The control rats were fed on standard chow. Blood glucose (G), serum insulin, serum leptin and serum lipids (triglycerides, total cholesterol, HDL-, LDL-, and VLDL cholesterol) were determined. Feeding with khat leaves reduced the body weight and the triglyceride level of the animals. The effect of KD on these parameters was stronger than that of KL. KD lowered the blood glucose concentration and the leptin content whereas KL was inactive. The khat intake had no significant influence on serum insulin, total serum cholesterol, HDL-, LDL- and VLDL-cholesterol.